Habilidades de visualização espacial na formação de professores de matemática - Silva, Cristian Martins da (2023)
Spatial Visualization Skills (SVS) can be defined as the ability to mentally visualize, manipulate and recognize an object. In the last two decades, a growing number of researches have discussed the potential of SVS as evidence and justification in teaching and learning problems in the area of Mathematics. Given its relevance in the context of Mathematics Education and its presence in Basic Education, mainly in Didactic Books (DB) and in the Exame Nacional do Ensino Médio (ENEM), it is understood the importance of addressing SVS in teacher training, and, in addition, the need to propose activities that develop SVS is evident. Therefore, a possible proposal is to associate these tasks with Digital Technologies (DT). In view of the above, the objective of this research is to investigate possibilities of working with SVS articulated with DT in a teacher training course. In this way, the present dissertation was structured in the format of articles, in which the five stages for the research are described: the first is the discussion of the theoretical aspects of SVS; the second consists of a mapping of dissertations on SVS; the third is the analysis of the presence of SVS in DB tasks; the fourth stage is the occurrence of questions present in ENEM tests that depend on the HVE to be resolved; the fifth step refers to the elaboration and application of a sequence of activities to develop SVS in a training course for Mathematics teachers. In this way, the first three stages of the investigation are characterized as Bibliographic Research, the fourth as Documentary Research and the last, being applied, as a Case Study. In this sense, based on the results of each stage, understand how some authors classify SVS, it was possible to place the research carried out in relation to the others selected in the mapping, evaluate how SVS are present in DB and how it is not broadly developed from of the analyzed categories, as well as in relation to ENEM questions that require certain visualization actions for resolution. Finally, the elaboration of a sequence of activities articulating the development of SVS with the use of DT showed how Dynamic Geometry Environments, in particular GeoGebra, played an important role in the exercise of spatial visualization with students of a teacher training course of math. In addition, this research found emerging difficulties in the development of SVS and expands the discussion on how to overcome these obstacles with the use of DT.